Аналіз роботи методу ієрарххічної міждоменної маршрутизації - Жуга, Ю. С. (ХНУРЕ, 2019)
The main idea of the model is its decomposition representation and formulation the inter-area interworking conditions. The implementation of these conditions guaranteed the connectivity of calculated inter-area paths. The proposed method is based on goal coordination principle that guaranteed the coordination procedure convergence in finite number of iterations which was confirmed on a set of examples.